2020
DOI: 10.1177/0003319720911572
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Essential Hypertension on Elasticity of Ascending Aorta in Type 2 Diabetic Mellitus Patients by Echocardiography

Abstract: Both essential hypertension (EH) and type 2 diabetes mellitus (T2DM) can impair the elasticity of the ascending aorta. We prospectively enrolled 42 patients with T2DM, 44 patients with EH, 45 patients with T2DM and EH (T2DM + EH), and 41 healthy subjects (HS). They all underwent transthoracic echocardiography to measure ascending aorta inner diameters and a brachial blood pressure measurement to calculate aortic elastic parameters (ie, compliance, distensibility, strain, stiffness index, and Peterson elastic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…23 Previous studies by our group have shown that T2DM can impair ascending aorta elastic properties which may be further impaired by poor blood glucose control. 4,24 In the present study, our results showed that compared with non-T2DM controls, the thickness of EAT was significantly higher in T2DM patients, which is consistent with previous studies. 25 Colom et al 26 found that EAT was associated with subclinical atherosclerosis of coronary arteries in patients with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…23 Previous studies by our group have shown that T2DM can impair ascending aorta elastic properties which may be further impaired by poor blood glucose control. 4,24 In the present study, our results showed that compared with non-T2DM controls, the thickness of EAT was significantly higher in T2DM patients, which is consistent with previous studies. 25 Colom et al 26 found that EAT was associated with subclinical atherosclerosis of coronary arteries in patients with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…So the early evaluation of ascending aorta elasticity has important clinical significance. Impaired elasticity of the ascending aorta in diabetic patients has been confirmed [9,32]. Toutouzas et al have demonstrated that the impairment of aortic elasticity is associated with the duration of diabetes [33].…”
Section: Discussionmentioning
confidence: 98%
“…Arterial stiffness is also closely related to diabetes, especially the elasticity of ascending aorta, is an important predictor of the incidence and death of various diseases. Studies have confirmed that there is damage to LV function and ascending aorta elasticity in patients with T2DM [7][8][9]. However, there is a paucity of research in the literature regarding whether there are any differences in LV function and ascending aorta elasticity between T2DM patients with controlled and uncontrolled blood glucose.…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of people, aortic aneurysms are incidental findings [ 51 ], which indicates the need for proper screening, as the mortality rate in acute aortic syndromes is still high [ 52 ]. In routine screening ultrasound tests, such as echocardiography, the ascending aorta is visualized [ 53 , 54 ] and its potential dilatation may be regarded as a potential indicator for further evaluation.…”
Section: Discussionmentioning
confidence: 99%